Physical activity, body weight, and resumption of menses in anorexia nervosa. (30th December 2016) - El Ghoch, Marwan; Calugi, Simona; Pellegrini, Massimo; Chignola, Elisa; Dalle Grave, Riccardo
Abstract: Few data are available on long-term outcomes and increased physical activity at the end of inpatient treatment in patients with anorexia nervosa. Hence we assessed the association between physical activity, measured objectively by Sense Wear Armband (SWA), and body mass index (BMI; kg/m 2 ) and menses resumption at one-year follow-up in 32 females with anorexia nervosa who had restored normal body weight by the end of a specialist inpatient treatment. Combined logistic regression models used to evaluate the relationship between variables at discharge, BMI and resumption of menses at one-year follow-up revealed no significant association between BMI at one-year follow-up and physical activity patterns at inpatient discharge. However, total daily steps at inpatient discharge were significantly lower in patients who had resumed menstruation, as confirmed by logistic regression analysis. A small reduction in daily steps at inpatient discharge ( 1000 steps) was found to increase the probability of menses resumption at one-year follow-up by 3%. These data provide preliminary indications as to the potential usefulness of assessing daily steps to predict the resumption of menses at one-year follow-up in patients with anorexia nervosa who restore body weight by the end of inpatient treatment, although confirmation on larger samples is urgently required. Highlights: No association between physical activity at inpatient discharge and one-year BMI. The daily steps at inpatient discharge were lower in who had resumed menstruation. A small reduction in daily steps seem to increase the probability of menses resumption.